Paddy farming and economies of size in Kuala Muda district - Mohayidin, Mohd Ghazali; Abd. Latif, Ismail (Universiti Putra Malaysia, 1994)
The aim of the paper is to analyse the relationship between farm sizes and the economies of size among paddy farmers in Kuala Muda District. Although Malaysia does not has comparative advantage in paddy production. the government has fully supported the paddy industry because of the security factors. Attempts are being made to modernize the sector further which includes mechanization that has been widely used by farmers so as to exploit the - timeliness -.efficiency and lower cost of operating the farm. This is expected to entail .the enlargement of farm size so that the economies of-size can be realized. Employing the Cobb-Douglas and. the Quadratic functions. various measures of costs and size elasticities were calculated. The results clearly showed the advantages of bigger farm size in reaping size economies. Cost reductions were significant in large.farms while the returns to farms were also economic. The average cost curves showed that larger farms can operate at a higher optimal production level at lower costs compared to the other smaller farm sizes. Cost economies were exhausted at relatively high levels of output. Thus farmers should expand their farm size so that they can exploit the benefits of size economies and operate at minimum cost levels. In cases where there are rigidities In the paddy land market. group farming and paddy mini estates should be encouraged so that efficiency in large scale operations can be realized.